Consumer Behavior Before and During the Covid-19 Pandemic in El Oro Province - Quizhpe-Bustos, Claudia Gabriela (2023)
The present investigation analyzes the impact of the pandemic on consumers' preferences, within the framework of electronic commerce to recommend market strategies that focus on consumers with more digital attention. For this reason, Wilcoxon’s statistical comparison of related samples has been used for non-parametric data in order to perform a comparison of frequencies between groups of different times that measured the behavior of users in this same range. The survey was used as a research tool and an increase in online purchases could be evidenced, highlighting the use of credit or debit cards and a reduction in purchases in physical establishments. In the case of the perception of electronic commerce, there was an increase in the sensation of ease, need and greater degree of usefulness about it. The results obtained demonstrate that the pandemic had a significant impact on consumer behavior and perceptions of electronic commerce in the study group.